2023
DOI: 10.3390/nu15153458
|View full text |Cite
|
Sign up to set email alerts
|

Linking Metallic Micronutrients and Toxic Xenobiotics to Atherosclerosis and Fatty Liver Disease—Postmortem ICP-MS Analysis of Selected Human Tissues

Abstract: Dyslipidaemia is a disorder of the lipid metabolism, caused mainly by poor eating habits. The most severe consequence of an inappropriate diet is the development of atherosclerosis and hepatic steatosis. It is generally believed that a change in nutrition, and increased physical activity can eliminate these health problems. The contemporary research and therapies used to treat dyslipidemia mainly focus on lowering the triglyceride and cholesterol levels. However, disturbances in trace element homeostasis or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 102 publications
(310 reference statements)
0
0
0
Order By: Relevance
“…A higher copper concentration was associated with an increased inflammatory response in patients referred for surgical coronary revascularization. Baj et al [35] determined the mineral profiles of liver and brain tissues collected at autopsy. They reported statistically significant higher concentrations of calcium and copper in the atherosclerosis group compared to patients with hepatic steatosis and concluded that the involvement of these elements is essential in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…A higher copper concentration was associated with an increased inflammatory response in patients referred for surgical coronary revascularization. Baj et al [35] determined the mineral profiles of liver and brain tissues collected at autopsy. They reported statistically significant higher concentrations of calcium and copper in the atherosclerosis group compared to patients with hepatic steatosis and concluded that the involvement of these elements is essential in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%